Democratic devices and desires - Brennan, Geoffrey (New York Cambridge University Press, 2000)
This book offers a novel approach to the analysis of democracy, and an application of that approach to a variety of democratic institutions, including elections, representation, political parties and the separation of powers. Standard economic approaches to politics concentrate on the design of institutions and the role of individuals motivated by self-interest. The authors incorporate a broader view of political motivation, assuming individuals are moral as well as rational, and provide a wide-ranging discussion of the design of democratic institutions.
Includes bibliographical references (p. 255-263) and index.
Keywords: Democracy--Economic aspects